Berberine-loaded polylactic acid nanofiber scaffold as a drug delivery system: The relationship between chemical characteristics, drug-release behavior, and antibacterial efficiency - Le, Le Thi; Nguyen, Hue Thi; Nguyen, Liem Thanh; Tran, Huy Quang; Nguyen, Thuy Thi Thu (Beilstein Journal of Nanotechnology, 2024)
Hydrophobic berberine powder (BBR) and hydrophilic BBR nanoparticles (BBR NPs) were loaded into an electrospun polylactic acid (PLA) nanofiber scaffold for modulating the release behavior of BBR in an aqueous medium. The BBR release from the BBR/PLA and BBR NPs/PLA nanofiber scaffolds was investigated in relation to their chemical characteristics, BBR dispersion into nanofibers, and wettability. The BBR release profiles strongly influenced the antibacterial efficiency of the scaffolds over time. When the BBR was loaded, the BBR/PLA nanofiber scaffold exhibited an extremely hydrophobic feature, causing a triphasic release profile in which only 9.8 wt % of the loaded BBR was released in the first 24 h. This resulted in a negligible inhibitory effect against methicillin-resistant Staphylococcus aureus bacteria. Meanwhile, the BBR NPs/PLA nanofiber scaffold had more wettability and higher concentration of BBR NPs dispersed on the surface of PLA nanofibers. This led to a sustained release of 75 wt % of the loaded BBR during the first 24 h, and consequently boosted the antibacterial effectiveness. Moreover, the cytotoxicity test revealed that the BBR NPs/PLA nanofiber scaffold did not induce any changes in morphology and proliferation of MA-104 cell monolayers. It suggests that the BBR/PLA and BBR NPs/PLA nanofiber scaffolds can be used in different biomedical applications, such as wound dressing, drug delivery systems, and tissue engineering, according to the requirement of BBR concentration for the desired therapeutic effects.
Keywords: antibacterial activity; berberine; drug-release system; electrospun nanofiber; polylactic acid